Using IT Design to Prevent Cyberbullying. Issue 3 (3rd July 2017) - Lowry, Paul Benjamin; Moody, Gregory D.; Chatterjee, Sutirtha
Abstract: The rise of social media has fostered increasing instances of deviant behavior. Arguably, the most notable of these is cyberbullying (CB), which is an increasing global concern because of the social and financial ramifications. This has necessitated a new line of research aimed at understanding and preventing CB. Although much progress has been made in understanding CB, little is known about how to prevent it, especially through the information technology (IT) design. Based on the need for a better causal theory and more effective empirical methods to investigate and mitigate this phenomenon, we leverage the control balance theory (CBT) for system design. Our model examines the causes of CB from several novel angles, including (1) the strong nonlinear influence of control imbalances on CB, and (2) using the concept of fit to understand how different design features of information technology artifacts influence factors such as deindividuation and accountability, thus affecting control imbalance. Using an innovative factorial survey method that enabled us to manipulate IT design features to obtain a nuanced view, we tested our model with 507 adults and found strong support for our model. The results show that IT design features create a strong CB opportunity for individuals who perceive that they are controlled by others. Whether this perception is real or imagined, it creates a sense of vulnerability, prompting them to engage in CB. We can thus propose specific IT design feature manipulations that can be used to discourage CB. These results should have salient implications for researchers and social media designers, especially in developing social media networks that are safe, supportive, responsible, and constructive.